1986
DOI: 10.1037/0021-843x.95.4.346
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption as a self-handicapping strategy in women.

Abstract: This experiment assessed whether women self-handicap with alcohol consumption prior to engaging in a social evaluation task, which may be more relevant to their self-esteem than the intellectual tasks used in past self-handicapping studies on substance use. In a 2 X 2 factorial design, 113 women who were evaluated as normal drinkers performed either a solvable or an insolvable social judgment task and then received either success feedback or no feedback. Subjects received access to alcoholic and nonalcoholic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In contrast, somatic anxiety stems from conditioned responses to aspects 2 of competition, such as the presence of an audience (Martens et al, 1990;Jones, 1995). As self-3 presentational concerns regarding an upcoming sports performance have been shown to be more 4 strongly correlated with cognitive than somatic sport competition anxiety (Bray,Martin,& 5 Widmeyer, 2000; Wilson & Eklund, 1998), it makes sense that a strategy designed to allay self-6 presentational concerns (i.e., self-handicapping), would have greater effects on cognitive than 7 somatic elements of anxiety. 8…”
Section: Self-handicapping and Anxiety In Sport 14mentioning
confidence: 99%
“…In contrast, somatic anxiety stems from conditioned responses to aspects 2 of competition, such as the presence of an audience (Martens et al, 1990;Jones, 1995). As self-3 presentational concerns regarding an upcoming sports performance have been shown to be more 4 strongly correlated with cognitive than somatic sport competition anxiety (Bray,Martin,& 5 Widmeyer, 2000; Wilson & Eklund, 1998), it makes sense that a strategy designed to allay self-6 presentational concerns (i.e., self-handicapping), would have greater effects on cognitive than 7 somatic elements of anxiety. 8…”
Section: Self-handicapping and Anxiety In Sport 14mentioning
confidence: 99%
“…Indeed, when faced with the clearly difficult task, mothers with a positive Family History in this sample showed the same pattern of SID as fathers. This contrasts with reported gender differences in the relationship between alcohol and stress 34–36 and suggests that the influence of family history may override gender effects. One study that investigated the stress‐response‐dampening (SRD) effects of alcohol reported that when family history of alcoholism was taken into account, men and women at high risk showed equivalent enhancement of an SRD effect 37 .…”
Section: Discussionmentioning
confidence: 61%
“…Nevertheless, Hirt, McCrea, and Boris (2003) examined gender differences in observer reactions to behavioral self-handicapping and showed that both males and females were critical of behavioral self-handicapping. Consequently, we chose one type of behavioral self-handicap (reveler drinker), considered to be maladaptive behavior and used by males and females (Berglas & Jones, 1978;Bordini, Tucker, Vuchinich, & Rudd, 1986). Some students often take part in a period of partying before a task completion.…”
mentioning
confidence: 99%